Simultaneous quantification of five biomarkers in ethanolic extract of Cassia occidentalis Linn. stem using liquid chromatography tandem mass spectrometry: application to its pharmacokinetic studies. Issue 8 (29th January 2020) - Riyazuddin, Mohammed; Husain, Athar; Verma, Saurabh; Katekar, Roshan; Garg, Richa; Kumar, Sudhir; Satish, Sabbu; Maurya, Rakesh; Narender, Tadigoppula; Chattopadhyay, Naibedya; Gayen, Jiaur R.
Abstract : Liquid chromatography tandem mass spectrometry was used to develop a bioanalytical method for simultaneous quantification of five biomarkers of Cassia occidentalis L. ethanolic extract to use in oral pharmacokinetics and in vitro stability studies. Abstract : Cassia occidentalis L. stem extract is used as a purgative, febrifuge, and diuretic, and in the treatment of flu, fever, fracture and bone diseases. Pharmacological studies prove the osteogenic and antiresorptive effects of Cassia occidentalis L. ethanolic extract (COEE), which may be due to apigenin, apigenin-6- C -glucopyranoside, luteolin, 3′, 4′, 7-trihydroxyflavone and emodin. The objectives of this study was to develop a selective and sensitive LC-MS/MS method and validate for the simultaneous determination of the above five biomarkers in rat plasma after oral administration of COEE at a dose of 500 mg kg −1 . The analytes were separated on a Phenomenex Luna C18 column (4.6 × 150 mm, 3.0 μm) with an isocratic mobile phase consisting of methanol-10 mM ammonium acetate buffer (95 : 05, v/v). Run time was for 5.5 min with LLOQ of 1 ng mL −1 for all the analytes. The mass spectrometer was operating in negative ionization mode for quantification of the analytes. The calibration curves were linear ( r 2 > 0.99) for all the analytes. The intra- and inter-day precisions were less than 8.17% and the relative error was between −8.57% and 7.28%. Analytes were rapidly absorbed in the oral pharmacokinetic study. The biomarkers were stable in simulated gastric and intestinal fluids but underwent metabolism in rat liver microsomes. This is the first report on in vivo oral pharmacokinetics and in vitro stability studies of osteogenic compounds present in COEE. These results will be helpful for further understanding of pharmacodynamic behaviour of COEE and the bioanalytical method will be useful for further preclinical/clinical trials.